Harmonic Reduction Of Transformer Based Cascaded H-Bridge Inverter Including Load Factor - Nandhini Gayathri M, Kannabhiran A, Kodeeswaran S (International Journal of Advanced Science and Technology, 2020)
This paper implements and analyses the performance of Transformer based multilevel inverter. In an ideal case, the THD (Total Harmonics Distortion) level of the multilevel inverter is equal to the predetermined. But in a typical case, the device voltage drop, non-integer voltage ratio and transformer voltage regulation affect the THD level. It causes an increase in its value. The objective of the multilevel inverter is to produce low distorted output. The aforementioned constraints increase a little bit. It can be reduced to the predefined by selecting proper step angles and dc voltage source ratios. The digital simulation and hardware implementation results validate the proposed technique.